A Projection-Type Method for Multivalued Variational Inequality - Changjie Fang; Shenglan Chen; Jiming Zheng (Abstract and Applied Analysis)
We propose a projection-type method for multivalued variational inequality. The iteration sequence generated by the algorithm is proven to be globally convergent to a solution, provided that the multivalued mapping is continuous with nonempty compact convex values. Moreover, we present a necessary and sufficient condition on the nonemptiness of the solution set. Preliminary computational experience is also reported.